Perceived barriers among cardiac patients towards cardiac rehabilitation programme - Sukhbeer Kaur Darsin Singh; Esther Jawing; Imran Zainal Abidin; Abqariyah Yahya; Anwar Suhaimi (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Cardiac rehabilitation is one of the secondary prevention programme to reduce morbidity and mortality in cardiac patients. However, adherence towards this programme is still sub optimal. The objective of this study isto determine the perceived barriers on cardiac rehabilitation programme among cardiac patients and its association with the sociodemographiccharacteristics. Methods: A preliminary study using the Cardiac Rehabilitation Barrier Scale (CRBS) was conducted in a tertiary hospital among 40 patients. The CRBS tool was validated and tested for reliability.Convenience sampling method was used among those who have attended the cardiac rehabilitation programme. Ethical approval was obtained from the institution ethical committee. There were total of 22 items in the CRBS except for the last item (22nd) being an open-ended item to enable the patients to share their opinion on any other barriers towards attendance to cardiac rehabilitation programme. The 21 items assessed on patients’ opinion on the perceived barriers during their attendance to the cardiac rehabilitation programme in a form of Likert scale. Results: The overall mean (SD) score for the 21 items was 60.70 (8.77) showed that the patients were able to understand gave their best options on the opinions towards CRBS. The highest mean on item 11 on ‘time constraints’ at 3.58 (0.75). Thus, the majority of the patients scored the item “time constraints’ as the highest perceived barrier during attendance in the cardiac rehabilitation programme. The association of the sociodemographic status had significance difference (p<0.05) for gender with item 4 on ‘family responsibilities’ and item 13 on ‘I don’t have energy’ with (p=0.035) and (p=0.020) respectively. Level of education too showed significant difference to item 9 on I find ‘exercise tiring and painful’ and item 12 on ‘work responsibilities’ with (p=0.034) and(p=0.048). Conclusion: Thus, measures should be taken for other barriers to ensure patients’ adherence to the cardiac rehabilitation programme.